A Stakeholder Accepted Tool to Monitor and Measure Service Delivery in South Africa - Mkhize, S'ngaye Christopher Phumlani (Graduate School of Business (GSB), 2023)
The aim of this study was to develop a stakeholder accepted tool to monitor and measure service delivery. The question underlying this research was what drives service delivery and its related protests and what makes it so problematic? The need for this study arose out of continued reports of these protests in South Africa. Evidence suggests that there may be a disconnect between the real experiences of communities on the ground and the causes cited by politicians and often reported in the media. The study used a mixed method approach to examine where the disconnect lies and built on the data to develop an audit tool. The study used primary and secondary data to understand the nature of service delivery and its related protests. The primary and secondary data provided both qualitative and quantitative data that highlighted the nature of service delivery landscape in South Africa. The quantitative data was instrumental in shaping and informing data collection protocol and shaping the draft tool for monitoring and measuring service delivery protest. Qualitative methods (i.e. interviews) were used to collect data in a purposive manner and to gather information from knowledgeable respondents and who are directly involved in service delivery. The findings showed that there is a disconnect in information sharing and knowledge between officials to the communities. The information was either not available at all or did not reach the intended recipients in order for them to make informed decisions. Furthermore, fake news from various sources clouded the communities from making sound judgments about their livelihoods. This disconnect may be regarded as a one of many fundamental reasons for the nature of service delivery protests in South Africa. The study also generated helpful insights and guided the development of a ‘service-delivery tool' for organisations and practitioners aiming to introduce and improve on their monitoring and evaluation framework for service delivery and its related protests.